Diagnóstico da mobilidade urbana sustentável através de indicadores na cidade de Aracaju-SE - Lucimara Dantas, Passos (2020)
The accelerated population growth and the high concentration of people in the cities impose great challenges to the development of urban mobility in a sustainable way. Problems common to Brazilian cities were established, among other factors, an excessive number of motor vehicles, on the roads, intended for individual transport, mass public transport expensive and unattractive to users and inadequate urban planning, which promotes public policies ineffective and postpone problem solutions. Universal access to public spaces is lacking. In view of this reality, it is imperative to deepen studies aimed at understanding this problem, which affects a large portion of the population of Brazilian cities. This research identified Indicators of Sustainable Urban Mobility in the city of Aracaju / SE, through the analysis of social, economic and environmental aspects that interfere in the Sustainable Urban Mobility (MUS) of the population. The research method was based on studies already carried out and validated by Costa (2008) and Miranda (2010), in the cities of São Carlos / SP, Curitiba / PR. The research result contributes to the implementation, monitoring and evaluation of public policies and highlights the weaknesses and potential of the existing model. The calculation of the proposed indicators, as well as the construction of the historical series, makes it possible to identify the ways to better the indicators that contribute negatively to sustainable urban mobility in Aracaju.